Resources for Apitourism in Bulgaria - GRIGOROVA, Zlatka; TIMAREVA, Stefka; SHOPOVA, Ivanka (Journal of Economic Development, Environment and People, 2016)
The report includes an analysis of the situation, trends and prospects of the resource base for the development of apitourism as an unconventional attractive and specialized type of supporting farmers through agricultural practices. The report presents the resource base (traditions, state, production and marketing of honey). For the aim of the analysis data has been used  from the National Statistics Institute, Ministry of Agriculture, Food beekeepers' associations, processors and traders of honey and bee products, the Ministry of Tourism and tourism industry organizations. The main purpose of the study is to assist companies and individuals in the field of agribusiness and apitourism for the realization of bee products and services.